Unreliable Evidence: 2 Sources of Uncertainty During Perceptual Choice - Michael, Elizabeth (Cereb Cortex, 2015)
Perceptual decisions often involve integrating evidence from multiple concurrently available sources. Uncertainty arises when the integrated (mean) evidence fails to support one alternative over another. However, evidence heterogeneity (variability) also provokes uncertainty. Here, we asked whether these 2 sources of uncertainty have independent behavioral and neural effects during choice. Human observers undergoing functional neuroimaging judged the average color or shape of a multielement array. The mean and variance of the feature values exerted independent influences on behavior and brain activity. Surprisingly, BOLD signals in the dorsomedial prefrontal cortex (dmPFC) showed polar opposite responses to the 2 sources of uncertainty, with the strongest response to ambiguous tallies of evidence (high mean uncertainty) and to homogenous arrays (low variance uncertainty). These findings present a challenge for models that emphasize the role of the dmPFC in detecting conflict, errors, or surprise. We suggest an alternative explanation, whereby evidence is processed with increased gain near the category boundary.